The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25030638
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliposomes and Tocosomes as Multifunctional Nanocarriers for the Encapsulation of Nutraceutical and Dietary Molecules

Abstract: Nanoscale lipid bilayers, or nanoliposomes, are generally spherical vesicles formed by the dispersion of phospholipid molecules in a water-based medium by energy input. The other nanoscale object discussed in this entry, i.e., tocosome, is a recently introduced bioactive carrier made mainly from tocopheryl phosphates. Due to their bi-compartmental structure, which consists of lipidic and aqueous compartments, these nanocarriers are capable of carrying hydrophilic and hydrophobic material separately or simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 115 publications
(170 reference statements)
2
26
0
Order By: Relevance
“…NLCs are another type of lipid-based nano carrier systems with colloidal particles composed of both solid and liquid lipids (Madane and Mahajan, 2016). Nanoliposomes provide a useful technology for delivering and targeting both hydrophilic and lipophilic phytobioactive constituents (Khorasani et al, 2018). Biodegradable polymeric NPs offer numerous advantages, since they protect bioactive constituents from degradation, enhance solubility, and provide controlled delivery and targeting (Pereira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…NLCs are another type of lipid-based nano carrier systems with colloidal particles composed of both solid and liquid lipids (Madane and Mahajan, 2016). Nanoliposomes provide a useful technology for delivering and targeting both hydrophilic and lipophilic phytobioactive constituents (Khorasani et al, 2018). Biodegradable polymeric NPs offer numerous advantages, since they protect bioactive constituents from degradation, enhance solubility, and provide controlled delivery and targeting (Pereira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years several food components and nutraceuticals have been encapsulated by different technologies [ 107 ]. One of the most common techniques that guarantees the stabilization of sensitive components, controlled release of core material, and that allows the physical separation of reactive or incompatible ingredients and thereby increasing product shelf-life is through the encapsulation technology [ 16 ].…”
Section: Challenges For New “Smart-foods” For Healthmentioning
confidence: 99%
“… Scheme of the most commonly applied nanocarriers for bioactive compounds [ 16 , 107 , 108 , 117 , 118 , 119 , 120 ]. …”
Section: Challenges For New “Smart-foods” For Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobic phytyl chains of T2P molecules cannot arrange in a parallel position because of the presence of bulky isoprene side-chains (unlike phosphatidylcholine and some other phospholipids). Accordingly, T 2 P possesses a conical geometric shape, while the TP has a cylindrical geometric shape, similar to PC [ 91 ]. Clinical studies have demonstrated that TP and T 2 P molecules have many advantages for human health, including atherosclerotic prevention as well as cardioprotective and anti-inflammatory properties [ 92 , 93 ].…”
Section: Vaccine Delivery Techniquesmentioning
confidence: 99%